2001
DOI: 10.1385/ir:24:1:31
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Signal Transduction and the Role of CD7 in Costimulation

Abstract: The complex cellular interactions that govern the mammalian immune response are now known to include specific receptor/ligand interactions, recruitment of intracellular signaling molecules, activation of both kinases and phosphatases, and redistribution of macromolecular complexes into specific subcellular membrane locations that, in aggregate, result in transcriptional activation. While the TCR-CD3 signal is critical for activation of the resting T cell, it alone is not sufficient to initiate transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 188 publications
(116 reference statements)
0
42
0
1
Order By: Relevance
“…CD7 is a cell surface glycoprotein member of the immunoglobulin superfamily and is found on thymocytes and mature T-cells. It plays an essential role in T-cell and T-cell/B-cell interactions during early lymphoid development (Stillwell and Bierer 2001). It has been reported that CD7 expression is up-regulated in chronic myeloid leukemia (CML) cells and in other leukemias and lymphomas (Rogers et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…CD7 is a cell surface glycoprotein member of the immunoglobulin superfamily and is found on thymocytes and mature T-cells. It plays an essential role in T-cell and T-cell/B-cell interactions during early lymphoid development (Stillwell and Bierer 2001). It has been reported that CD7 expression is up-regulated in chronic myeloid leukemia (CML) cells and in other leukemias and lymphomas (Rogers et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among the known costimulatory molecules, CD28 launches the most effective activation of T cells (Alegre et al, 2001;. However, recent reports have suggested that many other candidates, most of which reside in the lipid raft, induce T-cell activation as potently as CD28 does (Denning et al, 1988;Ledbetter et al, 1988;Green et al, 1994;Tai et al, 1996;Yashiro-Ohtani et al, 2000;Stillwell and Bierer, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Among the known costimulatory molecules, CD28 launches the most effective activation of T cells (Alegre et al, 2001;. However, recent reports have suggested that many other candidates, most of which reside in the lipid raft, induce T-cell activation as potently as CD28 does (Denning et al, 1988;Ledbetter et al, 1988;Green et al, 1994;Tai et al, 1996;Yashiro-Ohtani et al, 2000;Stillwell and Bierer, 2001).The lipid raft is a unique membrane microdomain that is enriched with specific types of lipids and cholesterol and is associated with many key molecules involved in TCR signaling. Upon engagement of cognate ligands (peptide/MHC), TCRs are recruited toward the raft along with a series of tyrosine-phosphorylated signaling molecules (Moran and Miceli, 1998;Xavier et al, 1998;Janes et al, 1999).…”
mentioning
confidence: 99%
“…27 CD7 has been recognized as a costimulatory molecule, leading to increased integrin adhesiveness through activation of phosphatidylinositol 3 (PI3) kinase. [28][29][30][31] Interestingly, CD7 is also necessary for induction of apoptosis in T cells by the ␀-galactoside-binding lectin galectin-1. 32-36 CD7 may thus play contrasting roles during different stages of an immune response.…”
Section: Introductionmentioning
confidence: 99%